2022
DOI: 10.1073/pnas.2123201119
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated incarceration and the public-housing-to-prison pipeline in New York City neighborhoods

Abstract: Using public housing developments as a strategic site, our research documents a distinct pathway linking disadvantaged context to incarceration—the public-housing-to-prison pipeline. Focusing on New York City Housing Authority (NYCHA) housing developments as a case study, we find that incarceration rates in NYCHA tracts are 4.6 times higher than those in non-NYCHA tracts. More strikingly, 94% of NYCHA tracts report rates above the median value for non-NYCHA tracts. Moreover, 17% of New York State’s incarcerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Despite these limitations, the evaluation findings suggest that BWCs, when deployed in the context of a court-mandated police reform regime, may help mitigate the harms generated by the "public housing to prison pipeline" that disproportionately incarcerates residents of Black and Hispanic neighborhoods with public housing present (Holder et al, 2022). Recent studies suggest that police officers are responsive to managerial directives (Mummolo, 2018;Rivera & Ba, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, the evaluation findings suggest that BWCs, when deployed in the context of a court-mandated police reform regime, may help mitigate the harms generated by the "public housing to prison pipeline" that disproportionately incarcerates residents of Black and Hispanic neighborhoods with public housing present (Holder et al, 2022). Recent studies suggest that police officers are responsive to managerial directives (Mummolo, 2018;Rivera & Ba, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of 2004-2011 stops, frisks, and arrests found that trespass stops and arrests in NYCHA public housing were two times greater than in the immediate surrounding area, and this difference was driven by increased percentages of Black and Hispanic populations in public housing (Fagan et al, 2012). A more recent analysis suggests that these enforcement and surveillance patterns were associated with a "public housing to prison pipeline" that disproportionately incarcerated residents of Black and Hispanic neighborhoods where NYCHA housing is present (Holder et al, 2022). In addition to allegations of unlawful and racially disparate stops and frisks, the 2010 Davis et al lawsuit contended that NYPD officers illegally detained and arrested NYCHA residents and their visitors on trespassing charges when they were not engaged in illegal activities nor on NYCHA property without proper authorization.…”
Section: Public Housing Crime and Aggressive Law Enforcementmentioning
confidence: 99%
“…JAYC works primarily with young Black and Hispanic New Yorkers, either themselves criminal legal system involved or closely connected to those impacted by the criminal legal system. It emphasizes building and strengthening organizational partnerships within historically underserved communities that are disproportionately impacted by gun violence, shootings, unemployment, and high levels of youth disconnect (see Fagan et al, 2002; Rosenfeld & Fornango, 2017; Holder et al, 2022). Jarrell Daniels founded the JAYC at Columbia University’s Center for Justice in 2018 after returning home from his own 6-year period of incarceration starting at age eighteen.…”
Section: Erf In Practice: the Jaycmentioning
confidence: 99%
“…Public housing developments are publicly-funded housing provided by the New York City Housing Authority (NYCHA) for more than 400,000 low-and moderate-income residents 35,36 , aiming to facilitate their access to public and community services. However, recent studies link NYCHA housings with dilapidated living conditions, high incarceration rate, and health risks [37][38][39][40] , establishing an eroded, disregarded, and harshly segregated figure. As a result, stakeholders are seeking to make public housing districts adequately invested and more inclusive [41][42][43] , where one of the most prominent efforts is the advocate for transit-oriented development, i.e., fundamentally integrating the development of affordable housing and accessible transit services 43,44 .…”
Section: Exploring Mitigation Policy Of Accessibility Inequalitymentioning
confidence: 99%